Walking Washington's History : Ten Cities - Bentley, Judy (Book collections on Project MUSE., 2016)
"Walking Washington's History : Ten Cities--a follow up to Bentley's Hiking Washington's History--seeks to provide a rich introduction to the history of the state through guided walks in ten significant cities, selected based on their size, walkability, and historical significance. The book begins with Vancouver, an early cosmopolitan settlement on the Columbia which brought together Chinook traders, British and American explorers, fur companies, missionaries, and settlers, and ends with Bellevue, a farming community turned bedroom community that did not incorporate until 1953 and was able to plan with a clean slate. In between, the book takes armchair and actual tourists through Olympia, Walla Walla, Tacoma, Seattle, Everett, Bellingham, Yakima, and Spokane, choosing a path through each that highlights aspects of Washington's history that are compelling to encounter in that particular place. Each chapter features a historical overview, a guided walk, and a map, and the book will include a modest selection of historical photos"--Provided by publisher.